Evaluation of a propolis hydroalcoholic solution with glycine in the joint reduction of microorganisms and helminth eggs from leafy green vegetables - Juliana da Silveira; Natália de Almeida Corrêa Alfredo; Marcia Regina Beux; Sila Mary Rodrigues Ferreira; Diego Averaldo Guiguet Leal (Brazilian Journal of Food Technology, 2023)
Abstract The main goal of this study was to evaluate the effectiveness of a propolis hydroalcoholic solution with glycine on the reduction of microorganisms and helminth eggs removal in lettuce leaves. Three experimental groups were evaluated in triplicate or replicates: microbiological (ME), parasitological (PE), and microbiological and parasitological (MPE). Before the experiments, the initial concentration of the native microbiota was assessed by counting mesophilic aerobes, molds and yeasts, using conventional microbiological techniques. Lettuce leaves were washed in tap water and subjected to different immersion treatments: propolis hydroalcoholic solution (PHS), propolis hydroalcoholic solution at pH 5.5 (PHS2), and propolis hydroalcoholic solution with glycine (PHS-glycine). In ME, propolis hydroalcoholic solution combined or not with glycine, was evaluated on the reduction of native microbiota. Residual microbiological contamination was assessed. In the PE, the effect of PHS2 and PHS-glycine was evaluated on the removal of a known number of Ascaris suum eggs on leaves artificially contaminated. In MPE, PHS-glycine was evaluated on the reduction of native microbiota and removal of eggs. A reduction of more than 2 log CFU/g was observed in ME. In PE, PHS-glycine removed 37.22% of eggs. In MPE, the PHS-glycine reduced 3.3 CFU/g of mesophilic aerobes, 5.0 log CFU/g of fungi, and 35.53% of eggs from vegetables. The results highlighted the solution’s efficiency in reducing or eliminating different contaminants in vegetables and reinforced the need for the development of hygiene methods that do not harm human health and are reproducible at the household level.